Implementing Enhanced Primary Care Registered Nurse Reimbursement in Rural Health Clinics: A Policy Analysis. (August 2021) - Switzer, Tina; Sawin, Erika Metzler; Eaton, Melody; Switzer, David; Lam, Christina; Robinson, Jamie; Elkins, Deborah
Rural Health Clinics (RHCs) were created in 1977 to address the high health care needs, limited provider access, and poor health outcomes of rural Americans. Although innovative at their inception, the provider-centric model of RHC cost-based reimbursement structures has not evolved, leaving limited opportunities for change; many have failed. Comprehensive, proactive change is needed. Registered nurses (RNs) working at the top of their practice scope are a neglected clinical resource that can improve access, quality, value, and satisfaction for rural patient communities. RHC reimbursement policy must evolve to sustain and support this significant RN role. RNs have demonstrated value in care continuity and disease management, but there is little research on the utilization of RNs using their enhanced skill set in RHCs. Using theBardach and Patashnik's eight steps of policy analysis, the authors will describe the background and regulations of RHCs, identify current barriers to improving the health of America's rural residents, and then provide evidence to support a new policy option according to the Quadruple Aim framework. The result is a sustainable policy recommendation designed to best serve rural communities.